Supplemental Nutrition Drinks: Do I Need Them? - Claire Marie Fassett; Nancy J. Gal; Wendy J. Dahl (EDIS)
Supplemental nutrition drinks are often used in hospitals and adult care homes to help nourish those who may be eating poorly and have lost weight due to illness or lack of appetite. More recently, these nutrition drinks have become available to purchase by consumers. Examples of common supplemental nutrition drinks or shakes are Ensure® and Boost®. This publication explores the question that many older adults ask: “Do I need supplemental nutrition drinks?”